Significant Factors Causing Cost Overruns In Telecommunication Projects In Nigeria - Ameh, Oko John; Soyingbe, Aliu Adebayo; Odusami, Koleola Tunwase (Penerbit Universiti Sains Malaysia, 2010)
Information and Communication Technology (ICT) provides enormous benefits to economic development. However, cost overruns are a worldwide phenomenon and pose a serious threat to the development of telecommunication infrastructure, which is the platform for ICT. It is imperative to examine the possible factors that could lead to cost overruns, in order to avert the associated catalytic effects on the development of other sectors of the economy. This study involves a questionnaire survey of 42 factors that were identified as having the potential to cause cost overruns in 53 telecommunication projects that are scattered over the six geopolitical zones in Nigeria. The results indicated that construction-related factors top the list of categories that cause cost overruns in telecommunication projects. The following factors were identified as major causes of cost overruns and are ranked in their order of importance: the lack of contractor experience on the telecommunication projects, the high cost of imported materials and the fluctuation in the prices of materials that are necessary for the telecommunication projects. The study recommends that contingency provisions should be put in place to mitigate these factors at the project conception stage.